Copy number gain of 11q13.3 genes associates with pathological stage in hypopharyngeal squamous cell carcinoma. Issue 3 (21st November 2016) - Pattle, Samuel B.; Utjesanovic, Natasa; Togo, Athena; Wells, Lucy; Conn, Brendan; Monaghan, Hannah; Junor, Elizabeth; Johannessen, Ingolfur; Cuschieri, Kate; Talbot, Simon
Abstract : Squamous cell carcinomas of the hypopharynx (HPSCC) and oropharynx (OPSCC) have markedly different patient outcomes. Differences in HPV prevalence between these two patient groups may account for some of this difference, but other molecular markers of prognosis or pathological phenotype have not been established. Copy number gain of oncogenes is a well‐established molecular change contributing to HNSCC development. Quantitative PCR was used to explore copy number gains of specific genes (3q— PIK3CA, TP63; 11q13.3 —CCND1, ANO1 ) in tumor DNA recovered from HPSCC ( n = 48) and OPSCC ( n = 52) patients. Associations between copy number gain, patient demographics, HPV/p16INK4a status and pathological stage were examined. HPV/p16 prevalence in HPSCC and OPSCC groups was 2.1% and 46.0%, respectively. HPSCCs had frequent gains of CCND1 (56.3%) and ANO1 (56.3%) but few gains of PIK3CA (6.3%). By contrast, OPSCCs had significantly fewer CCND1 (23.1%) and ANO1 (17.3%) gains, and significantly more PIK3CA (26.9%) gains. A mutually exclusive relationship between HPV/p16 and 11q13.3 gains was observed in OPSCCs, while PIK3CA and TP63 gains were similar across HPV‐associated and smoking/alcohol‐associated patients. ANO1 gain was significantly linked to tumor pathology in HPSCC, associating with nodal metastasis and smaller and less invasive tumors at presentation ( P = 0.010). Our results provide a convincing link between a specific molecular change and disease phenotype that appears unique to our HPSCC population, supporting a model of 11q13.3 in promoting metastatic disease progression in HNSCC, and suggest a role for ANO1 as a molecular marker of metastatic disease. © 2016 Wiley Periodicals, Inc.